2007
DOI: 10.1590/s0047-20852007000300001
|View full text |Cite
|
Sign up to set email alerts
|

Tendência temporal da esquizofrenia: um estudo realizado no âmbito hospitalar

Abstract: 35.35% (4,501). The stay length in the hospital was 44.33 ± 36,9 days, compared to 29.5 ± 61.6 days for non-schizophrenic patients (p < 0.0001

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Paranoid schizophrenia was considered the most common diagnosis (60.2%), followed by residual schizophrenia (7.5%) and hebephrenic schizophrenia (5.2%). Other studies conducted in Brazil found paranoid schizophrenia in 40 to 43.7% of the patients (Messias et al, 2000;Ferreira et al, 2007). Some of the comorbidies reported were already associated with schizophrenia.…”
Section: Discussionmentioning
confidence: 82%
“…Paranoid schizophrenia was considered the most common diagnosis (60.2%), followed by residual schizophrenia (7.5%) and hebephrenic schizophrenia (5.2%). Other studies conducted in Brazil found paranoid schizophrenia in 40 to 43.7% of the patients (Messias et al, 2000;Ferreira et al, 2007). Some of the comorbidies reported were already associated with schizophrenia.…”
Section: Discussionmentioning
confidence: 82%
“…Schizophrenia also has an average age of hospitalizations close to 40 years [12][13][14] , and like bipolar disorder, it is a chronic and progressive disease. This, coupled with the fact that some disorders -such as depressive disorders -peak at 30 years of age 15 , can explain the 30-59 age group as having the highest hospitalization rate.…”
Section: Discussionmentioning
confidence: 99%
“…Estudo realizado por uma pesquisadora brasileira apontou que fatores como ser do sexo feminino, não residir no município do hospital ou no entorno hospitalar e passar por processo de internação compulsória tendem a aumentar a média de permanência hospitalar de pacientes com esquizofrenia, consequentemente elevando o custo das internações 21 . Também é importante destacar a maior prevalência da doença em indivíduos do sexo masculino, os quais apresentam maior exposição ao uso de substâncias psicoativas e menor adesão ao tratamento medicamentoso, o que contribui para a ocorrência de crises psicóticas 22 .…”
Section: Métodounclassified